Correlative Localization Analysis Between mRNA and Enhanced Green Fluorescence Protein-Fused Protein by a Single-Molecule Fluorescence in situ Hybridization Using an egfp Probe in Aspergillus oryzae - Morita, Yuki; Katakura, Yoshinori; Takegawa, Kaoru; Higuchi, Yujiro (Frontiers in Fungal Biology, 2021)
Although subcellular localization analysis of proteins fused with enhanced green fluorescence protein (EGFP) has been widely conducted in filamentous fungi, little is known about the localization of messenger RNAs (mRNAs) encoding the EGFP-fused proteins. In this study, we performed single-molecule fluorescence in situ hybridization (smFISH) using an egfp probe to simultaneously visualize EGFP-fused proteins and their mRNAs in the hyphal cells of the filamentous fungus Aspergillus oryzae. We investigated the subcellular localization of mRNAs encoding cytoplasmic EGFP, an actin marker protein Lifeact tagged with EGFP, and several EGFP-fused proteins AoSec22, AoSnc1, AoVam3, and AoUapC that localize to the endoplasmic reticulum (ER), the apical vesicle cluster Spitzenkörper, vacuolar membrane, and plasma membrane, respectively. Visualization of these mRNAs by smFISH demonstrated that each mRNA exhibited distinct localization patterns likely depending on the mRNA sequence. In particular, we revealed that mRNAs encoding Lifeact-EGFP, EGFP-AoSec22, EGFP-AoVam3, and AoUapC-EGFP, but not cytoplasmic EGFP and EGFP-AoSnc1, were preferentially localized at the apical cell, suggesting certain mechanisms to regulate the existence of these transcripts among hyphal regions. Our findings provide the distinct localization information of each mRNA in the hyphal cells of A. oryzae.